Narrowed Lives Meaning, Moral Value, and Profound Intellectual Disability - Vehmas, Simo (Stockholm University Press, 2021)
What is day-to-day life like for people with profound intellectual and multiple disabilities who live in group homes? How do they express their desires and wishes? How do care workers think about them and treat them? Do they have basic rights to activities most of us take for granted: activities like sociability, sexuality, and moral affirmation? Narrowed Lives is an illuminating portrait of what life is like in Finnish group homes where adults who have profound intellectual and multiple disabilities live their lives. Based upon ethnographic data, it documents how care workers strive to guarantee individuality and dignity against a backdrop of scarce resources and misguided policies. This book argues that the lives of people with profound disabilities need not be determined by their impairments. It calls for a re-evaluation of disability policy so that its underlying conviction of people with profound intellectual and multiple disabilities as equally valuable fellow humans would materialise in practice. This novel and accessible book combines ethnography and philosophy, and will be of interest to researchers and students in disability studies, special education and philosophy, as well as parents, professionals and policy makers. Endorsements from Readers For people with profound intellectual and multiple impairments, what is a good life? Who is responsible for trying to ensure that such a life is possible? This sobering, no-nonsense book about individual people who live in Finnish care homes is a timely and vital contribution to thinking about both the possibilities and the limitations of care, empathy and moral engagement. - Don Kulick, Distinguished University Professor of Anthropology, Uppsala University This important book boldly challenges many pervasive and harmful assumptions about people with profound disabilities. Through powerful illustrations of how the external world can constrain, limit, and deny the worth of disabled persons, the authors confront difficult but essential questions that must be asked in order to combat ableism and enable flourishing. By combining philosophical analysis with in-depth research into lived experience and relationships, this book is a call to critically reconsider how meaning is assigned, and how moral values are embodied in everyday practices. Narrowed Lives boldly asserts that the varied and complex lives of people with profound disabilities need not be narrow at all. - Licia Carlson, Professor of Philosophy, Providence College Provocative... this book provides answers to questions of the human that unconsciously abound in any conception of intellectual disability and, crucially, urges all researchers to consider the lives of people with intellectual disabilities. - Dan Goodley, Professor of Disability Studies and Education, University of Sheffield